Cost-Effectiveness of the “Helping Babies Breathe” Program in a Missionary Hospital in Rural Tanzania - Vossius, Corinna (Public Library of Science, 2014)
OBJECTIVE: The Helping Babies Breathe” (HBB) program is an evidence-based curriculum in basic neonatal care and resuscitation, utilizing simulation-based training to educate large numbers of birth attendants in low-resource countries. We analyzed its cost-effectiveness at a faith-based Haydom Lutheran Hospital (HLH) in rural Tanzania. METHODS: Data about early neonatal mortality and fresh stillbirth rates were drawn from a linked observational study during one year before and one year after full implementation of the HBB program. Cost data were provided by the Tanzanian Ministry of Health and Social Welfare (MOHSW), the research department at HLH, and the manufacturer of the training material Lærdal Global Health. FINDINGS: Costs per life saved were USD 233, while they were USD 4.21 per life year gained. Costs for maintaining the program were USD 80 per life saved and USD 1.44 per life year gained. Costs per disease adjusted life year (DALY) averted ranged from International Dollars (ID; a virtual valuta corrected for purchasing power world-wide) 12 to 23, according to how DALYs were calculated. CONCLUSION: The HBB program is a low-cost intervention. Implementation in a very rural faith-based hospital like HLH has been highly cost-effective. To facilitate further global implementation of HBB a cost-effectiveness analysis including government owned institutions, urban hospitals and district facilities is desirable for a more diverse analysis to explore cost-driving factors and predictors of enhanced cost-effectiveness.